Calvin and humanism - Peyer, Iso (Trinity College (Dublin, Ireland). Department of History, 2003)
Calvin and humanism is an extensive and controversial topic the treatment of which depends to a considerable extent on the type of approach and method adopted. The introduction provides an overview of the special difficulties involved in exploring the question of Calvin's relation to humanism, specifying their implications for research, and it situates the topic in the wider context of intellectual and religious history, namely the development of the relationship between the Reformation and humanism since Luther. Among the special difficulties encountered three are prominent. First, the reformer shows a fundamentally reserved attitude towards humanism manifest in his conspicuous lack of explicitness concerning the principal issues associated with it. Calvin's reticence to address humanistic subjects directly can be described in terms of "implicitness", marginalisation or even tabooisation, and it makes the elaboration of a coherent theory based on documentary evidence a hard task. Second, humanism is the object of an ongoing controversy which is embedded in deep-rooted intellectual divisions, and therefore no agreed definition exists. This means that any conclusions about the relation of the Reformation to humanism depend substantially on the concept of humanism adopted. Third, Calvin's insistence on rational clarity contrasts sharply with the humanists' espousal of literary ambiguity. This contrast indicates a fundamental antagonism which makes the direct comparison of the two movements difficult. Chapter one offers an overview of the literature, distinguishing four different types of interpretation. These types are advocated by major scholars, which demonstrates that no agreement on the question of Calvin and humanism has been reached. Augustijn and Crouzet defend an anti-humanistic interpretation (Calvin is averse or hostile to humanism), Neuser and Parker a non-humanistic one (Calvin is indifferent to or reserved about humanism), McGrath and Muller a scholastic one (Calvin shows distinct affinities with late medieval thought), and Millet, Bouwsma and Oberman a humanistic one (Calvin is a humanist or is friendly towards humanism). In chapter two the main problems of defining humanism are analysed and a concise integral description of the movement is provided. In defining humanism the conflict between philosophical (Garin) and anti-philosophical (Kristeller) interpretations is taken into account, since conclusions about Calvin and humanism depend essentially on the attitude adopted towards that issue. It appears impossible to bridge the gap between the philosophical and the anti-philosophical interpretations of humanism, which are rooted in distinct and long-established intellectual traditions in modem European thought (going back to Vico and Descartes). Since an adequate treatment can only be reached if a twin-track approach integrating both views is adopted, equal attention is given to the ideal of humanitas (emphasised by the philosophical interpretation of humanism) and to the cycle of the studia humanitatis (emphasised by the philosophical interpretation of humanism). Chapters three and four provide an analysis of humanism according to the criteria of the studia humanitatis. Chapter three looks at the subjects of grammar, rhetoric, poetry and history, while chapter four deals with the philosophical components of humanism (among which moral philosophy features prominently). A close consideration of the philosophical interpretation suggests that the humanists embraced a fundamentally anthropocentric outlook in which the factor of self-knowledge played a key role as human existence was understood in terms of self-realisation. The ideal of humanitas implied the establishment of a harmonious balance between the individual faculties of the mind, which required the promotion of the undervalued non-rational faculties (imagination, will, memory) against the dominance of reason in scholasticism. This aspect of humanist intellectual reformism has been epitomised in terms of a shift from ratio to oratio and it has been manifest most prominently in the humanists' anti-philosophical polemic and in their defence of freedom and the imagination in the framework of the disciplines of moral philosophy and poetry. If humanist reformism is considered in this way as a protest against the increasing tide of rationalism (encountered in Aristotelianism), humanitas can be interpreted as corresponding to an affirmation of what is today referred to as unconsciousness (according to Fromm's suggestion), and therefore the humanists can be seen as early advocates of the unconscious and the humanist movement as fostering a process of expansion of consciousness. This contrasts with the prevailing intellectual currents of the Renaissance, which tended to amplify the conscious sphere of the human mind, thus encouraging the development or promotion of consciousness. Chapter five deals with the young Calvin, whose relation to humanism is difficult to determine due to a lack of source material. Taking into account the latter fact, the chapter not only offers an overview of the literature but also provides a summary of the (often neglected) early biographies. However, no conclusive statements can be made concerning the attitude of the young Calvin towards humanism, so that his intellectual disposition cannot with any degree of certainty be determined as predominantly humanistic or scholastic before his religious conversion. It is possible that Calvin underwent an intellectual conversion in his youth, leading him from the espousal of a nominalistic epistemology to the adoption of a compromise between a humanistic and a realistic theory of knowledge, which was not uncommon in the later Renaissance. It remains uncertain whether there existed a period in the life of the young Calvin which was dedicated exclusively or predominantly to humanistic pursuits. Probably humanism became a hobby for Calvin when he turned from legal to religious studies, thus playing an auxiliary role in the shaping of his religious views. In chapter six the relation of Calvin the reformer to humanism is analysed using the concept of humanism elaborated in chapters two, three and four. Calvin's attitude towards the studia humanitatis is examined with regard to the humanistic programme of studies as a whole as well as with regard to the individual disciplines of that cycle of studies, taking into account the reformer’s view of the related notion of humanitas. Unlike most humanists, Calvin disassociates the concepts of humanitas and the studia humanitatis, treating the latter with a considerable degree of detachment while almost completely disregarding the former. Calvin hardly ever deals with humanism or humanistic issues in an explicit or direct way, sidelining humanistic questions in such a way that his attitude can be characterised in terms of "implicitness", marginalisation or even tabooisation (if unconscious factors are also considered). The reformer never formally condemns humanism or the humanistic studies but he never delivers a wholehearted or unreserved recommendation and his manner of talking about humanistic themes sometimes almost amounts to condemnation. On the whole Calvin maintained a distinctly critical attitude towards humanism and the humanities. This is most obvious in his reservations about the art of poetry, which was absolutely central to humanism and from which he detached himself almost completely. Calvin's "implicitness" concerning humanism and his marginalisation of it suggest the existence of a degree of tabooisation, that is, an unconscious desire to suppress humanism. Calvin is not categorically and completely against humanism but he prefers to keep it on a low level because he is apprehensive about the possible philosophical liberating effects which the outlook associated with it might have. Thus, on the whole the studia humanitatis can be useful instruments for theology but they must be "helpers" performing an auxiliary function and never become "masters". The renaissance of letters is interpreted by Calvin according to Luther’s theological framework: the humanistic studies were revived by God in order to further the cause of the Gospel and restitute the Bible in its original form. With his rational focus on theology and in particular the Bible Calvin can be characterised as a "pre- Cartesian philosopher" who is a typical representative of the Renaissance insofar as he advocates what we have called promotion of consciousness, that is, he defends the emphasis on the conscious side of the human mind (as found in most forms of Aristotelian philosophy). His preoccupation with imposing limits to human understanding and, in a wider sense, to the human urge for knowledge, reveals him as someone who resists what we have called expansion of consciousness, for which the humanists called. Thus Calvin is at odds with the impulses arising from the realm of humanitas or the human unconscious and does not encourage, as has been claimed, a quest for wholeness.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin